2005
DOI: 10.1080/00167223.2005.10649529
|View full text |Cite
|
Sign up to set email alerts
|

Reading remittance landscapes: Female migration and agricultural transition in the Philippines

Abstract: In the Philippines, female migration for overseas contract work is transforming local agricultural landscapes. Yet the changes in land, labour, crops and cropping patterns that are occurring may not reflect local ecology or economic opportunity as much as they represent gendered versions of local modernity, envisioned at a new global scale. This study links local agricultural change to local interests in global migration and reads local landscapes as reflecting those links.Drawing on interviews and observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 11 publications
0
64
0
Order By: Relevance
“…In her work in the Philippines, McKay (2005) found women's migration to be both cause and result of a move from subsistence to intensive commercial agriculture, with remittances capitalizing the transition. In this regard, Gray's recent quantitative study in Ecuador is a helpful addition to the literature, as he separates migration's remittance effect from its labor effect and identifies differences based on the gender of the migrant (Gray 2009).…”
Section: Literature Reviewmentioning
confidence: 97%
“…In her work in the Philippines, McKay (2005) found women's migration to be both cause and result of a move from subsistence to intensive commercial agriculture, with remittances capitalizing the transition. In this regard, Gray's recent quantitative study in Ecuador is a helpful addition to the literature, as he separates migration's remittance effect from its labor effect and identifies differences based on the gender of the migrant (Gray 2009).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Among these studies, several have found evidence of disintensification of agriculture (Zimmerer 1993; Preston et al 1997; Schmook and Radel 2008; Jones 2009; Qin 2010; Robson and Berkes 2011), while others have observed small or zero net effects (Black 1993; Klooster 2003) or intensification through the investment of remittances (McKay 2005; Taylor et al, 2006; De Haas 2006). Three studies have examined Ecuador specifically.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Others have examined the effect of remittances on land use [41,42]. In the context of the Philippines, for example, McKay [43,44] has written of "remittance landscapes", highlighting the way in which the effects of migration can be seen inscribed in the fields of the Ifugao: "Bean gardens can be read as remittance landscapes-they both anticipate remittances and produce the capital needed to go overseas-and are thus tied to the translocal nature of apparently local places" ([43], p. 306). Work in Cambodia has also shown how migration interlocks with farming, reshaping the latter in the process, leading to both a feminization and a geriatrification of farming [45].…”
Section: Teleconnections and Telecouplingmentioning
confidence: 99%